Inisiasi Agro-eduwisata Petik Jeruk di Teaching Factory Kebun Inovasi Polije - Marseva, Amalia Dwi; Sumarlina, Sumarlina; Nadhirah, Aulia; Napitupulu, Tia Sofiani; Putri, Chintya Jessica (SEJAGAT : Jurnal Pengabdian Masyarakat, 2025)
Teaching Factory (TeFa) Kebun Innovation is one of the TeFa at Politeknik Negeri Jember which focuses on the production of food crop commodities and horticulture. One of the commodities cultivated at TeFa Kebun Inovasi is orange. There are 7 types of oranges cultivated at TeFa Kebun Inovasi. TeFa has the potential to be developed as an agro-tourism destination with 4,000 m2 of land planted with oranges. Agro-edutourism is a type of tourism that combines agriculture and education as its main objects. However, TeFa does not yet have an agro-educational tourism plan. For this reason, an agro-educational tourism initiative was carried out at TeFa Kebun Inovasi. Initiation activities are carried out through five stages, namely preliminary survey, focus group discussion, identification of tourism potential, mentoring, and monitoring and evaluation. The evaluation results show that the agro-edutourism initiation activities have improved the knowledge, skills, and management ability of the management team in designing agro-edutourism, delivered by the agenda of orange picking tour.